Застосування теорії свідчень у адаптивних курсах корпоративних систем дистанційного навчання - Іларіонов, Олег Євгенович; Іларіонова, Ніна Миколаївна; Сорока, Петро Миколайович (НТУ "ХПІ", 2016)
Розглянуто перспективи застосування окремих математичних інструментів для адаптації курсів у корпоративних системах дистанційного навчання. Ідентифіковано особливості корпоративних систем дистанційного навчання – характеристики осіб, що навчаються, характеристики навчальних курсів та показники ефективності. Показано, що адаптація дистанційних курсів у таких системах повинна відбуватися передусім на основі аналізу компетенцій. Компетенції визначаються в результаті тестування та аналізу результатів тесту за допомогою теорії свідчень Демпстера-Шафера. Подальша адаптація курсів відбувається за допомогою моделі генерації контенту на основі компетенцій.

Perspectives to use some mathematical instruments to adapt e-learning courses in corporate area are considered. Analysis of corporate e-learning systems showed that the level of prior knowledge, skills, and abilities (competencies) of learners is one of the most important criteria effectiveness of education and should serve as a basis for courses customization. Pretest can be conducted using multiple choice questions where there is a relationship between questions and concepts, and this relationship has weights. The evidences obtained from pretest are combined using Dempster’s combination rule to find the real level of competences of the learner. These values are used as an input incompetency-based content generation model. The approach offered by the authors is not free of the drawbacks. First, any tests are associated with errors and mistakes. Also, there is a need of fuzzification of intervals obtained from evidence combinations. Content generation model requires a lot of learning objects that together with input profile might lead to issues with finding the optimal decision. Also, teachers should invest a lot of efforts to create appropriate test questions and learning objects.
Evidence theory in adaptive corporate e-learning systems
Keywords: теорія Демпстера-Шафера; навчальний профіль; адаптивні моделі; корпоративне дистанційне навчання; компетенції; Dempster-Shafer theory; learning profile; adaptive models